Applications of the internet of things for optimizing warehousing and logistics operations: A systematic literature review and future research directions. (September 2022) - Kumar, Devinder; Kr Singh, Rajesh; Mishra, Ruchi; Fosso Wamba, Samuel
Highlights: IoT applications for optimizing warehousing and logistics operations are focused. Majority of studies on IoT in warehousing and logistics conducted in developed world. In comparison to logistics, studies on warehousing are slowly gaining attention. There is an under-representation of various theories in IoT research. Future research areas discussed using Theory, Methodology, and Context framework. Abstract: The introduction of Industry 4.0 technologies such as the Internet of Things (IoT), artificial intelligence (AI), cloud computing, and others has revolutionised the traditional warehousing and logistics industry, resulting in significant changes to various operations and decision-making. Despite the undeniable importance of this topic, the primary research on the impact of IoT technology is inconsistent and scattered. The present study aims to review state-of-art literature on the application of IoT technology in the warehousing and logistics field and suggests a path for the future research through an in-depth analysis of studies done in this area. Sixty-four research articles were carefully selected after a thorough search of the Scopus and EBSCO databases, covering the period from January 2011 to 07th December 2021, to examine the applications of the IoT in the warehousing and logistics business. These articles were thoroughly reviewed and classified in terms of year-wise distribution, major publication outlets, types of study, and highly cited papers to understand the evolution and ongoing trends in this field. The findings reveal that majority of the studies on IoT in the warehousing and logistics domain have been conducted in developed countries. While logistics has been widely investigated, studies on the warehousing domain are limited. Also, there is an under-presentation of various theories in IoT research. The study highlights various gaps by synthesising existing literature and provides a fertile ground for conducting future research in this domain. Supply chain practitioners and researchers will find this review timely and valuable, which offers several valuable implications for them.